Complex Nanomaterials: Laser‐Directed Self‐Organization and Reaction Control in Complex Systems: A Facile Synthesis Route for Functional Materials (Adv. Mater. Interfaces 2/2014). Issue 2 (April 2014) - Reinhardt, Hendrik; Pietzonka, Clemens; Harbrecht, Bernd; Hampp, Norbert
<x xml:space="preserve">Abstract</x> The back cover displays a colored electron microscopy image of vertically aligned nanorod arrays consisting of graded transition metal oxides. Nanomaterials of such complexity are considerably difficult to create using standard processes. As N. Hampp and co‐workers report in article 1300060, directed self‐organization in multicomponent precursors appears to be a powerful concept for this upcoming challenge in nanoscience. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>